Evaluation of the quality of life of patients before treatment of squamous cell carcinoma of the head and neck by means of chemoradiotherapy - Visacri, Marília Berlofa; Ferrari, Graziele Baldan; Pimentel, Rafaela; Ambrósio, Rosiane D. Fátima Lopes; Lima, Carmen Silvia Passos; Mazzola, Priscila Gava; Moriel, Patricia (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : To identify predictors of quality of life (QOL) in head and neck cancer patients prior to cisplatin chemotherapy and radiotherapy treatment. Material and methods : A cross-sectional study at a Clinical Oncology department of a teaching hospital in the state of São Paulo, Brazil, from September 2011 to October 2012 was performed. QOL was assessed using the University of Washington QOL Questionnaire. Demographic and clinical characteristics were obtained through interviews with patients and collected from medical records. Multivariate linear regression was used to determine the association between QOL scores and patient-related factors. Results : We studied 48 head and neck cancer patients, who were mostly white (77.1%), males (83.3%), with pharyngeal cancers (66.7%), cancers with stage T4 (45.8%) and N1 (31.2%) tumours, and classified with a Karnofsky Performance Status (KPS) of 90% (37.5%). Patients had excellent scores for saliva (96.2 ±13.5) and shoulder (93.6 ±17.9), with pain and anxiety being the most affected domains (59.6 ±32.4 and 57.5 ±39.2, respectively). A significant relationship of KPS and T stage with overall QOL score was noted. The population with lowest overall QOL score was those who had low KPS scores and T4 tumours. Conclusions : Head and neck cancer patients prior to cisplatin chemotherapy and radiotherapy treatment, with a low KPS and staged as T4 tumours, have worse overall QOL, and special attention should be given to these patients.